2014
DOI: 10.1177/0894439314521982
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between E-Social Networks and the Communication Behaviors of Generation 2000 (Millennials) in Turkey

Abstract: The information revolution has shaped a new generation. Our study focused on the relation between the social networks that benefit from the opportunities arising from information technologies and the communication behaviors of Generation 2000 university students. According to the findings of this research, in Turkey, university students’ use of mobile Internet and social networks is increasing and becoming widespread when compared to that observed in the previous years. For both Generation 2000 and others in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Some of these results, which are in line with the results of this study, showed that the use of Internet media was associated with lower levels of social isolation (4,41). On the contrary, limited studies show opposite results (26,42).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some of these results, which are in line with the results of this study, showed that the use of Internet media was associated with lower levels of social isolation (4,41). On the contrary, limited studies show opposite results (26,42).…”
Section: Discussionsupporting
confidence: 90%
“…The results show that young people use the Internet more than middle-aged people. In line with some other studies (5,26,27), Internet use reduces social isolation and its dimension in both young and middle-aged people. In summary, the results of this study showed that Internet use does not have any effect on the reduction or increase in the number of members of each individual's CDN.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Currently, the use of VCs is increasing, and this tendency will continue in the future in several contexts such as politics (Gable, 2015;Zhang, Johnson et al, 2010), education (Latif, Uçkun, & Demir, 2015;Slavich & Zimbardo, 2012), or work and commercial practice (Aghakhani, Karimi, & Salehan, 2018;Li & Lee, 2013), among others. The globalization of advanced societies is leading to a highly virtualized, hyperconnected world.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphones have become essential in modern daily life. The so-called millennials, those belonging to the age groups 18–24 and 25–34 years (Howe & Strauss, 2007; Latif et al, 2015) make up the largest group of smartphone users (“Smartphone Owner Penetration,” 2017). The most notable applications on the smartphones of these young people are SNSs (“Millennials Are Top,” 2016), and the first thing these millennials do in the morning is to check their social media accounts (“Social Media Is,” n.d.).…”
Section: Smartphone Development and Inclusion In Family Dinners At Homementioning
confidence: 99%